De oprichting van de ‘Nederlandsche Vereeniging voor Tropische Geneeskunde’: een zaak van nationaal belang - van Bergen, Leo (Studium, 2009)
The foundation of the Dutch Society for Tropical Medicine: an affair of national importance The ‘Nederlandsche Vereeniging voor Tropische Geneeskunde’ (Dutch Society for Tropical Medicine – in short: NVTG) was founded in 1907, a time not only of colonial expansion, but also a time in which the economic interest of the Dutch East-Indies for the Netherlands grew exceptionally. This had its effect on the motivations behind medical aid. Hygienic measures were financially backed because healthy workers had a positive effect on profits. This atmosphere of economic interest and political-military expansion had its effect on the foundation of the NVTG as well. Colonialism was generally approved of, and the goal of the society – apart from sociability motives – was to support research into illnesses torturing mainly the Dutch colonies. This was in line with the reasoning that the colonies were rightfully governed by the Netherlands, because the peoples living there had proven not to be able to look after themselves in a proper manner. The foundation of the Society should have been a part of the foundation of an international society for tropical medicine, but this failed. Although internationalism generally was seen as an important feature of science and certainly of medical science, it is not strange this was not seen as a major problem. For it was national and not international reasons that had led to founding the Dutch society. It was the Dutch position as a colonial power that had convinced Dutch tropical doctors a society should be called into being. A generally shared spirit of internationalism had little to do with this unless internationalism is defined as: what others have, we need to have as well, and let us see in international conferences what could be of national benefit. That nevertheless this spirit of internationalism – and not nationalism – is commonly hailed as the main reason behind the foundation, is probably due to the fact that around 1900 nationalism was such a normal state of mind and so fully incorporated in man’s way of thinking and acting, that, as for instance was the case with racism, it was hardly noticed and recognised as such.